The Value of Gotong-royong in the Mountainous Settlement of Kepuharjo Village at Pagerjurang Permanent Shelter in Yogyakarta, Indonesia (International Journal of Built Environment and Sustainability, 2021)
Providing housing for refugees due to disasters is a common problem in countries prone to natural disasters. The eruption of Mount Merapi in Yogyakarta in 2010 has displaced the people of Kepuharjo Village to a new settlement in Pagerjurang permanent shelter. However, the process of settling in a new settlement requires adjustments because the people of Kepuharjo Village have been living on the slopes of Mount Merapi for generations. This research is a qualitative research which aims to find a reflection of the space-occupancy value system that occurs in the village of Kepuharjo at the Pagerjurang permanent shelter. The results of observations and interviews with 29 units show that the description of the activities and arrangement of the residential space in the Pagerjurang permanent shelter. The results showed that the motivation for the development of residential spaces is closely related to kinship and socio-cultural values in the daily life of the occupants. The socio-cultural reflection on the residential space of the Kepuharjo community in the Pagerjurang permanent shelter is in line with the social principles of mutual-cooperation (gotong-royong). Gotong-royong is expressed in the strengthening of space, expansion of space, and agreement of space.
Keywords: Dwelling Space; Gotong Royong; Housing; Socio-cultural; Value